The Story of Al-Kindi: Rhetoric of Argumentation: From Submissiveness and Coaxing to Persuasion and Manipulation - Mohammad Sarhan, Haitham (Al-Adab Journal, 2020)
This article seeks to unearth the structures of argumentation that are employed in the story of Al-Kindi, which was included in Al-Jahiz’s Kitab al-Bukhala’ (The Book of Misers). The Story, which features tenants’ attempts to take advantage of property laws in order to (mis)use Al-Kindi’s private property, captures Al-Kindi undermining the tenants’ efforts by using a myriad of pretexts and justifications, both real and unreal.Approaching this story, this article relies on the principles of argumentation theory in its focus on communicative dimensions of the text, highlighting the main argumentative styles that Al-Kindi uses to produce a discourse that protects his rights against unfair treatment. The article highlights the strategies that move Al-Kindi’s argumentation from convincing and persuading the tenants to committing epistemic violence against them through mentally and psychologically manipulating and winning them over in order to subdue them. The article concludes that the story of Al-Kindi includes surface and deep messages. While the surface of the story is built around a discourse of stinginess and parsimony, the deep meaning concerns the rhetorical strategies through which a questioning of the existing cultural norms and metaphors is established in order to enable the audience discover the inherent contradictions and paradoxes that lie within these norms.